Detection and characteristic analysis of the crustal basement interface in Guangxi, China - Lu, Zhongxu; Yang, Fuqiang; Yang, Yang; Liao, Haizhi; Mo, Yajun (Frontiers in Earth Science, 2025)
To analyze the three basement interfaces of the crust in Guangxi, China (the Crystalline Basement Interface, the Conrad discontinuity, and the Moho discontinuity), seismic and gravity exploration were conducted. First, the depth values of the crustal interfaces, obtained from seismic data within the study area, were used as constraints. Gravity data were then employed to investigate the undulating morphology of the basement surfaces. Second, through gravity field separation techniques, density interface fitting inversion was performed to infer the undulating morphology of the Guangxi Crystalline Basement Interface, the Conrad discontinuity, and the Moho discontinuity. Depth distribution maps of these interfaces were created, and characteristic analyses were carried out. The results show that there is a certain inheritance relationship between the Crystalline Basement Interface, the Conrad discontinuity, and the Moho discontinuity in Guangxi, with the crust being thicker in the northwest and thinner in the southeast (the mantle subsides downward in the northwest and uplifts in the southeast). The spatial attributes of the Guilin-Hezhou mantle subsidence zone and the Yuchengling new mantle amalgamation body were analyzed. Additionally, by combining the detailed field characteristics of wavelet analysis, it is suggested that the crust of Guangxi exhibits a grid-like, framework regional structural pattern, clarifying the distribution laws of major granite belts. These belts develop along the mantle subsidence zones and are controlled by deep faults. The research results can provide important references for studies on deep structures and other related fields in Guangxi.